2017
DOI: 10.1016/j.bbagrm.2016.08.004
|View full text |Cite
|
Sign up to set email alerts
|

The RNAs of RNA-directed DNA methylation

Abstract: Summary RNA-directed chromatin modification that includes cytosine methylation silences transposable elements in both plants and mammals, contributing to genome defense and stability. In Arabidopsis thaliana, most RNA-directed DNA methylation (RdDM) is guided by small RNAs derived from double-stranded precursors synthesized at cytosine-methylated loci by nuclear multisubunit RNA Polymerase IV (Pol IV), in close partnership with the RNA-dependent RNA polymerase, RDR2. These small RNAs help keep transposons tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
112
2
2

Year Published

2017
2017
2019
2019

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 134 publications
(120 citation statements)
references
References 110 publications
(219 reference statements)
0
112
2
2
Order By: Relevance
“…Alu siRNA increased methylation specifically in Alu elements exhibiting sequence identity to the siRNA sequence without significantly methylating LINE-1, another IRS. This finding suggests that siRNA-induced methylation in humans using a mechanism similar to RNA-directed DNA methylation (RdDM) in plants [37]. Of note, scramble siRNA could promote a variable degree of Alu methylation possible because the scramble siRNA may be able to bind some of Alu elements and consequently methylated CpGs.…”
Section: Discussionmentioning
confidence: 98%
“…Alu siRNA increased methylation specifically in Alu elements exhibiting sequence identity to the siRNA sequence without significantly methylating LINE-1, another IRS. This finding suggests that siRNA-induced methylation in humans using a mechanism similar to RNA-directed DNA methylation (RdDM) in plants [37]. Of note, scramble siRNA could promote a variable degree of Alu methylation possible because the scramble siRNA may be able to bind some of Alu elements and consequently methylated CpGs.…”
Section: Discussionmentioning
confidence: 98%
“…In the major RdDM pathway (reviewed in: Matzke and Mosher, 2014; Wendte and Pikaard, 2017), NUCLEAR RNA POLYMERASE IV (Pol IV) and RNA-DEPENDENT RNA POLYMERASE 2 (RDR2) generate short double-stranded RNAs that are then diced into 24 nt short interfering RNAs (siRNAs) (Blevins et al, 2015; Li et al, 2015; Zhai et al, 2015). These siRNAs associate with an Argonaute family protein, primarily AGO4 or AGO6, and guide cytosine methylation through basepairing interactions with nascent Pol V transcripts (Wierzbicki et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In yeast, these nascent RNAs are generated by RNA polymerase II (Pol II), whereas, in Arabidopsis, they are generated by Pol V, a plant-specific evolutionary derivative of Pol II (Wendte and Pikaard 2016). Studies in both organisms have demonstrated that target loci need to be transcribed in order to be silenced and that Ago can be coimmunoprecipitated in association with RNAs derived from silenced loci (Motamedi et al 2004;Irvine et al 2006;Wierzbicki et al 2009;You et al 2013).…”
mentioning
confidence: 99%
“…The process is particularly well studied in Schizosaccharomyces pombe and Arabidopsis thaliana, which have in common the fact that the requisite siRNAs are diced from double-stranded precursor RNAs made via the combined actions of DNA-dependent and RNA-dependent RNA polymerases. The siRNAs are then loaded into Argonaute (Ago) proteins that nucleate assembly of multiprotein silencing complexes at loci that are complementary to the siRNAs (Holoch and Moazed 2015;Wendte and Pikaard 2016).…”
mentioning
confidence: 99%